2024
DOI: 10.3390/en17030550
|View full text |Cite
|
Sign up to set email alerts
|

Economic Dispatch Optimization Strategies and Problem Formulation: A Comprehensive Review

Fatemeh Marzbani,
Akmal Abdelfatah

Abstract: Economic Dispatch Problems (EDP) refer to the process of determining the power output of generation units such that the electricity demand of the system is satisfied at a minimum cost while technical and operational constraints of the system are satisfied. This procedure is vital in the efficient energy management of electricity networks since it can ensure the reliable and efficient operation of power systems. As power systems transition from conventional to modern ones, new components and constraints are int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 206 publications
0
3
0
Order By: Relevance
“…Considering these factors is vital to prevent equipment damage, cut operating costs and enhance overall efficiency within integrated power systems. Below, we outline the contribution of this study, emphasizing the comparison with the results reported by the authors in [27,28,[32][33][34][35][36][37]:…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Considering these factors is vital to prevent equipment damage, cut operating costs and enhance overall efficiency within integrated power systems. Below, we outline the contribution of this study, emphasizing the comparison with the results reported by the authors in [27,28,[32][33][34][35][36][37]:…”
Section: Introductionmentioning
confidence: 86%
“…The third approach is presented in Equation ( 5), which utilizes a piecewise method to depict the segments that form the cost curve. This representation differs from the mathematical models published in the literature [27,28,[32][33][34][35][36][37], we propose to incorporate a binary variable that simplifies the choice of a single operating state for the CCPP. It focuses exclusively on the two non-convex states of the CCPP, which enable a transition between them, and the binary variable facilitates its selection efficiently.…”
mentioning
confidence: 99%
“…Simultaneously, the problem must adhere to system constraints and address environmental concerns to minimize pollution from thermal power plants. Mathematically, the EED issue is nonconvex [5,6], involving inconsistent objectives and non-linear restrictions derived from power flow limitations, grid compliance requirements, valve point impacts, and prohibited operating zones for units. Efficient algorithms are necessary to find the optimal trade-off between environmental and economic considerations.…”
Section: Introductionmentioning
confidence: 99%